2021
DOI: 10.1177/0018720821991651
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of the SEEV Model as a Process Measure of Situation Awareness: The Example of a Simulated Endotracheal Intubation

Abstract: Objective In the context of anesthesiology, we investigated whether the salience effort expectancy value (SEEV) model fit is associated with situation awareness and perception scores. Background The distribution of visual attention is important for situation awareness—that is, understanding what is going on—in safety-critical domains. Although the SEEV model has been suggested as a process situation awareness measure, the validity of the model as a predictor of situation awareness has not been tested. Method I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Such validation is accomplished by correlating the SEEV-predicted PDTs with the % scans or percentage dwell time (PDT) on each AOI. It has been used both to predict the overall scanning behavior of users, but also, in some circumstances, to characterize the differences between novice and expert scan patterns (Grungeiger et al, 2021;Koh et al, 2011;). An important difference here is that experts should be more calibrated to the true expected value of an AOI, and less "distracted" or influenced by the two nuisance parameters of salience and effort.…”
Section: Supervisory Controlmentioning
confidence: 99%
“…Such validation is accomplished by correlating the SEEV-predicted PDTs with the % scans or percentage dwell time (PDT) on each AOI. It has been used both to predict the overall scanning behavior of users, but also, in some circumstances, to characterize the differences between novice and expert scan patterns (Grungeiger et al, 2021;Koh et al, 2011;). An important difference here is that experts should be more calibrated to the true expected value of an AOI, and less "distracted" or influenced by the two nuisance parameters of salience and effort.…”
Section: Supervisory Controlmentioning
confidence: 99%
“…Supporting this argument, empirical studies have shown that including salience (Steelman et al, 2011) or effort (Grundgeiger, Beckh, et al, 2020; Wickens et al, 2008) did not increase model fit of expert participants. Finally, a study (Grundgeiger et al, in press) indicated a positive association between EV model fit and situation awareness level 1 (perceiving events in the environment; Endsley, 1995) which further supports the idea that good EV model fit indicates an advantageous visual attention distribution. Therefore, the EV model fit also provides the opportunity to draw a conclusion about the quality of the visual attention distribution.…”
Section: Introductionmentioning
confidence: 55%
“…Compared to previous model attempts in healthcare, the current model fits are slightly worse. One explanation might be the less structured and more stressful emergency situation in the present study compared to common situations such as the uneventful induction of general anesthesia (Grundgeiger et al, in press; Grundgeiger, Wurmb, et al, 2020) or scrub nursing during caesarean section surgery (Koh et al, 2011). In the literature, staff reported such an emergency situation effect, in particular for the first minutes of CPR (Sachedina et al, 2019; Sjöberg et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations